Liquidity Risk on Banking Industry: Comparative Study Between Islamic Bank and Conventional Bank in Indonesia - Muharam, Harjum; Kurnia, Hasna Penta (Faculty of Shariah and Law, 2013)
Conventional and Islamic banks approximately are similar in risk summary. Therefore it needs further observations to control their liquidity risk. This study investigates the influence of CAR, profitability rasios, NIM, liquidity gaps, and RLA belongs to liquidity risk on banking industry. The statistical analysis concluded that there are negative and significant influence of CAR and ROE to liquidity risk on conventional banks, while ROA and RLA have positive and significant effect. In Islamic banks, a positive and significant impact of NIM and ROE to dependent variable, whereas liquidity gaps and RLA have significat effect.DOI: 10.15408/aiq.v5i2.2118